Finansowo-prawne instrumenty kształtowania niepodatkowych dochodów własnych gmin o charakterze publicznoprawnym - Kowalczyk, Rafał (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2019)
In the monograph Finansowo-prawne instrumenty kształtowania niepodatkowych dochodów własnych gmin o charakterze publicznoprawnym (Financial and legal instruments of shaping communes' non-tax own revenue of public and legal character), the author (on the principle of a negative catalogue) made a selection and legal analysis of all those incomes that are not included in the group of tax revenues, and at the same time (within the positive catalogue) determined which of those incomes meet the criteria for considering them as own revenue of a public nature. The impulse to undertake the analysis of this group of revenues was the lack of comprehensive legal studies concerning non-tax revenues of public communes. Meanwhile, even a preliminary analysis of the normative layer in the scope of this income leads to the conclusion that it is differentiated, not only due to its legal nature, but also due to the non-uniform and often incomplete legal regulation, which creates conditions for legal discourse. Therefore, the main task was to subject a comprehensive analysis of a selected income group, both in terms of normative construction, place in the income system of local government units, and above all (which in the author's opinion seems to be particularly important), an attempt was made to assess the scope of eligibility delegated to commune bodies in order to shape the construction of these incomes. Nevertheless, it was important to determine the existence and identification of other functions (apart from fiscal) performed by the revenues indicated in terms of the subject matter. The subjective scope of the conducted research covered the incomes of communes with regard to the commune's position in the structure of the local government, as well as (or maybe first of all) the complexity of the structure of the unit's own income. Since communes are the basic local government units with the longest history of functioning, combining it with the greatest diversity of their income has naturally created a ground for fruitful considerations. The internal structure of the work was based on two main parts of the study, the first of which was devoted to general issues of systematizing and synthetic value. Whereas the second part of the work was devoted to specified in the first part groups of income consisting of non-tax own income of a public nature, and the whole study was summarized with conclusions.
Keywords: own revenue; commune; authority; legal instrument; public fees